The Effect of E-Wallet Usage and Digital Financial Literacy on Digital Investment Decisions among Generation Z: The Mediating Role of Financial Self-Efficacy - Ranty Pratiwi; Adnan Kasofi; Osly Usman; Ryna Parlyna (Asosiasi Transformasi Digital Dan Bisnis Indonesia, 2026)
Digital investment behavior among Generation Z has attracted increasing attention alongside the widespread use of digital financial services in Indonesia. This study explores the relationship between e-wallet usage, digital financial literacy, and digital investment decisions by considering financial self-efficacy as an intervening factor. Data were collected through a cross-sectional survey of Generation Z individuals who actively use e-wallet services and were analyzed using regression-based and mediation techniques. The findings reveal that e-wallet usage and digital financial literacy are associated with higher financial self-efficacy, which in turn contributes significantly to digital investment decisions. Moreover, e-wallet usage and digital financial literacy continue to show direct relationships with digital investment decisions after accounting for financial self-efficacy, indicating partial mediation. Overall, the results suggest that digital investment decisions are shaped not only by digital engagement and financial knowledge but also by individuals’ perceived ability to manage financial matters.